Detrital diversity influences estuarine ecosystem performance. (12th March 2013) - Kelaher, Brendan P.; Bishop, Melanie J.; Potts, Jaimie; Scanes, Peter; Skilbeck, Greg
Abstract Global losses of seagrasses and mangroves, eutrophication‐driven increases in ephemeral algae, and macrophyte invasions have impacted estuarine detrital resources. To understand the implications of these changes on benthic ecosystem processes, we tested the hypotheses that detrital source richness, mix identity, and biomass influence benthic primary production, metabolism, and nutrient fluxes. On an estuarine muddy sandflat, we manipulated the availability of eight detrital sources, including mangrove, seagrass, and invasive and native algal species that have undergone substantial changes in distribution. Mixes of these detrital sources were randomly assigned to one of 12 treatments and dried detrital material was added to seventy‐two 0.25 m2 plots (n = 6 plots). The treatments included combinations of either two or four detrital sources and high (60 g) or low (40 g) levels of enrichments. After 2 months, the dark, light, and net uptake of NH4+, dissolved inorganic nitrogen, and the dark efflux of dissolved organic nitrogen were each significantly influenced by the identity of detrital mixes, rather than detrital source richness or biomass. However, gross and net primary productivity, average oxygen flux, and net NOX and dissolved inorganic phosphorous fluxes were significantly greater in treatments with low than with high detrital source richness. These results demonstrate that changes in detrital source richness and mix identity may be important drivers of estuarine ecosystem performance. Continued impacts to estuarine macrophytes may, therefore, further alter detritus‐fueled productivity and processes in estuaries. Specific tests that address predicted future changes to detrital resources are required to determine the consequences of this significant environmental problem.